2008
DOI: 10.1007/s12013-008-9035-2
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent Activation of Neurons by Continuous Near-infrared Laser

Abstract: Optical control of neuronal activity has a number of advantages over electrical methods and can be conveniently applied to intact individual neurons in vivo. In this study, we demonstrated an experimental approach in which a focused continuous near-infrared (CNI) laser beam was used to activate single rat hippocampal neurons by transiently elevating the local temperature. Reversible changes in the amplitude and kinetics of neuronal voltage-gated Na and K channel currents were recorded following irradiation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 31 publications
1
31
1
Order By: Relevance
“…S3). Although the rate of temperature increase with this approach was much slower than that seen in infrared laser-based heating approaches (44,45) or the rapid solution-switching approach (46), it was sufficient to reach activation temperature in 1-2 seconds.…”
Section: Methodsmentioning
confidence: 83%
“…S3). Although the rate of temperature increase with this approach was much slower than that seen in infrared laser-based heating approaches (44,45) or the rapid solution-switching approach (46), it was sufficient to reach activation temperature in 1-2 seconds.…”
Section: Methodsmentioning
confidence: 83%
“…To characterize heat-induced activation kinetics, a rapid laser heating approach was used (25). Briefly, a 1443-nm laser diode (Fitel) with controllers (Thorlabs) was used to generate a continuous narrow laser beam.…”
Section: Methodsmentioning
confidence: 99%
“…We characterized the activation kinetics of the heteromeric channels. To ensure that the rate of temperature change was much faster than the rate of channel activation, we employed a laser heating method (25) to heat the patch pipette tip above 45°C in less than 30 ms. Recording from inside-out patches held at ϩ80 mV, we observed that the heteromeric channels and the homomers exhibit marked differences in the activation rate in response to heating (Fig. 7A).…”
Section: Formation Of Functional Heteromeric Trpv1/trpv3mentioning
confidence: 99%
“…The linearity found in both temperature increases and changes in firing rate by optical stimulation in our study supports the findings that neuronal modulations are due to the transient temperature increase and increased temperature in thermodynamic equilibrium induced by optical stimulation. 3,28 We were able to induce significant neuronal excitations and inhibitions in the subcortical structures using NIS at power of >20 mW. In addition, it was found that optical stimulation at a power of 20 mW led to a temperature increase of about 2°C.…”
Section: Threshold In Laser Power and Temperaturementioning
confidence: 89%
“…Regarding the mechanism of neuronal activation changes by optical stimulation, Liang et al 28 reported the elevated local tissue temperature as a cause of changes in the activity of a single hippocampal The asterisks (*, **, and ****) indicate statistical significance at different levels (p < 0.05, p < 0.005, and p < 0.0001, respectively) comparing beforeduring, during-after, and before-after. Fig.…”
Section: Continuous Nis At 808 Nm Can Modulate Neuralmentioning
confidence: 99%